1977
DOI: 10.1007/bf00318346
|View full text |Cite
|
Sign up to set email alerts
|

The fine structure of human digital arterio-venous anastomoses (Hoyer-Grosser's organs)

Abstract: Hoyer-Grosser's organs were studied in human digital biopsies. The fine structure of both the supplying arteries and collecting veins was found to be inconspicuous. Endothelial cells in the AV canals form a continuous layer. They are characterized by their rich content of specific organelles (Weibel-Palade bodies), especially in the venous segments. The epitheloid zone is composed of a variety of ramified smooth muscle cells (RSM). These appear either dense, when well provided with bundles of myofilaments, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 36 publications
1
15
0
1
Order By: Relevance
“…Rewarming kinetics of the hands has been successfully used to assess the effects of surgical sympathetic block previously [19].We confirmed that the main effect of the ESB is observed in the fingertips, as would be expected according to the rich vasoconstrictory innervation of the arterio-venous shunts in the fingertips [6,12]. ESB at the level of T4 was by far less effective in suppressing vasoconstrictor outflow and also in reducing palmar sweating as compared to ESB at T2.…”
Section: Discussionsupporting
confidence: 76%
“…Rewarming kinetics of the hands has been successfully used to assess the effects of surgical sympathetic block previously [19].We confirmed that the main effect of the ESB is observed in the fingertips, as would be expected according to the rich vasoconstrictory innervation of the arterio-venous shunts in the fingertips [6,12]. ESB at the level of T4 was by far less effective in suppressing vasoconstrictor outflow and also in reducing palmar sweating as compared to ESB at T2.…”
Section: Discussionsupporting
confidence: 76%
“…16 The abundance of D␤H-ir fibers around the canal suggests their function in blood flow regulation. 11 Our data show that AVAs also present VIP-ir fibers that could be sensitive 12 or more likely, parasympathetic 8 with a role in vasodilation. 17 The presence of myelinated fibers supplying AVAs suggests that their main afferences are fast conducting fibers, able to detect to rapidly changing hemodynamic conditions.…”
Section: Discussionmentioning
confidence: 91%
“…Their constituents include a small feeding artery, a small canal (Suquet-Hoyer canal) with a virtual space delimited by an endothelium and a very thick collagen wall and a draining vein. 11 We observed a heavy innervation surrounding the canal, whereas nerves were less abundant around the feeding artery and sparse around the draining vein ( Fig 1A). The PGP-ir fibers around the canal presented a wavy ribbon-like shape at high magnification.…”
Section: Arterio-venous Anastomosesmentioning
confidence: 93%
“…The carotid arteriovenous anastomoses have been localized, as demonstrated by simultaneous injections of radioactive microspheres of different sizes, particularly in the skin, ears and dura mater, but also in the eyes and tongue (Saxena & Verdouw, 1985;Den Boer et al, 1992). Although arteriovenous anastomoses are anatomically distinct from the rest of the microvasculature, light and electron microscopy studies have shown the presence of an endothelial layer in both human and rabbit peripheral arteriovenous anastomoses (Gorgas et al, 1977;Fujiwara & Iijima, 1990). The finding that L-arginine, the endogenous substrate for NO-synthase, partly reversed the L-NAME-induced reductions in the carotid arteriovenous anastomotic blood flow and conductance suggests that NO, released from the endothelium, may provide a vasodilator tone in these specialized vessels.…”
Section: Discussionmentioning
confidence: 99%